2023
DOI: 10.3390/ijms24087065
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipid Metabolism Enzymes in Rat Epididymal Fat after Chronic Central Leptin Infusion Are Related to Alterations in Inflammation and Insulin Signaling

Abstract: Leptin inhibits food intake and reduces the size of body fat depots, changing adipocyte sensitivity to insulin to restrain lipid accrual. This adipokine may modulate the production of cytokines that could diminish insulin sensitivity, particularly in visceral adipose tissue. To explore this possibility, we examined the effects of chronic central administration of leptin on the expression of key markers of lipid metabolism and its possible relationship with changes in inflammatory- and insulin-signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Furthermore, leptin administration induced a reduction in lipoprotein lipase and carnitine palmitoyl-transferase-1A expression, together with a decrease in the phosphorylation of insulin-signaling targets and a low-grade inflammatory pattern. In conclusion, they demonstrated that central leptin infusion regulated lipid metabolism, reducing epididymal fat stores and suggesting its use as a modulating agent in obesity [ 10 ]. Finally, in a very interesting paper, Di Maio and colleagues evaluated the ability of some drugs, including GW501516, sildenafil, and rosiglitazone, and Irisin, a myokine that is stimulated by muscular exercises, to induce the browning process of white adult adipocytes obtained from differentiated mesenchymal stromal cells (MSCs).…”
mentioning
confidence: 99%
“…Furthermore, leptin administration induced a reduction in lipoprotein lipase and carnitine palmitoyl-transferase-1A expression, together with a decrease in the phosphorylation of insulin-signaling targets and a low-grade inflammatory pattern. In conclusion, they demonstrated that central leptin infusion regulated lipid metabolism, reducing epididymal fat stores and suggesting its use as a modulating agent in obesity [ 10 ]. Finally, in a very interesting paper, Di Maio and colleagues evaluated the ability of some drugs, including GW501516, sildenafil, and rosiglitazone, and Irisin, a myokine that is stimulated by muscular exercises, to induce the browning process of white adult adipocytes obtained from differentiated mesenchymal stromal cells (MSCs).…”
mentioning
confidence: 99%